Diagnostic approach to the evaluation of myeloid malignancies following CAR T-cell therapy in B-cell acute lymphoblastic leukemia. Issue 2 (27th November 2020) - Mo, George; Wang, Hao-Wei; Talleur, Aimee C; Shahani, Shilpa A; Yates, Bonnie; Shalabi, Haneen; Douvas, Michael G; Calvo, Katherine R; Shern, Jack F; Chaganti, Sridhar; Patrick, Katharine; Song, Young; et al.
Abstract : Immunotherapeutic strategies targeting B-cell acute lymphoblastic leukemia (B-ALL) effectively induce remission; however, disease recurrence remains a challenge. Due to the potential for antigen loss, antigen diminution, lineage switch or development of a secondary or treatment-related malignancy, the phenotype and manifestation of subsequent leukemia may be elusive. We report on two patients with multiply relapsed/refractory B-ALL who, following chimeric antigen receptor T-cell therapy, developed myeloid malignancies. In the first case, a myeloid sarcoma developed in a patient with a history of myelodysplastic syndrome. In the second case, two distinct events occurred. The first event represented a donor-derived myelodysplastic syndrome with monosomy 7 in a patient with a prior hematopoietic stem cell transplantation. This patient went on to present with lineage switch of her original B-ALL to ambiguous lineage T/myeloid acute leukemia. With the rapidly evolving field of novel immunotherapeutic strategies, evaluation of relapse and/or subsequent neoplasms is becoming increasingly more complex. By virtue of these uniquely complex cases, we provide a framework for the evaluation of relapse or evolution of a subsequent malignancy following antigen-targeted immunotherapy.